Facilitating health care workers' self‐determination: The impact of a self‐leadership intervention on work engagement, health, and performance. Issue 2 (5th May 2021) - van Dorssen‐Boog, Pauline; van Vuuren, Tinka; de Jong, Jeroen P.; Veld, Monique
Abstract : The present study aims to test the impact of a self‐leadership intervention on the work engagement, performance, and health of health care workers. By integrating self‐determination theory and self‐leadership theory, we propose that when employees are trained how they can autonomously influence own cognitions and behaviour, this will impact their work engagement, perceived performance, and general health. To test the hypotheses, a longitudinal field experiment with three measurement waves was conducted (pre‐intervention, immediately after the intervention, and 2 months after the intervention). Health care professionals ( n = 195) from five different organizations participated on voluntary basis and were randomly assigned to the intervention or control group. Results show that a self‐leadership training positively impacts work engagement and performance of health care workers. Furthermore, the improved work engagement also mediates the effects of the training on health and performance 2 months later. No direct effect was found on general health. Theoretical and practical implications are discussed. Practitioners points: The self‐leadership intervention facilitates healthcare workers to develop self‐determination and autonomous motivation, which will positively impact their work engagement, health, and performance Participation in the self‐leadership intervention needs to be based on volition as this will contribute to the intrinsic motivation for actual self‐leadership development through training.